Pendekatan Model Vector Autoregression untuk Analisis Pertumbuhan Pembiayaan (Studi pada PT Pegadaian Kabupaten Nganjuk) - Laili Agustin, Maya; Ayu Paramitha, Dyah; Faisol, Faisol (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
This study aims to analyze the response of the amount of financing to changes that occur in the variables of the number of customers, interest rates, and income at PT Pegadaian (Persero) Nganjuk. The data used in this study is secondary data, in the form of time series in 36 months sourced from PT Pegadaian (Persero). The analytical method applied is vectorauto regression (VAR) with the help of STATA 14 sofware. The results show that the variable number of customers shows a negative response bacause the decrease or increase in the number of customers does not affect credit financing. Then the interest rate variable responds positively, meaning that an increase in interest rates will have an impact on increasing credit financing as well. Furthermore, the income variable responds positively to credit financing, meaning that an increase in income will have an impact on increasing financing.